Implementation of the Rapid Application Development Method in the Development of a Web-Based Information System for Monitoring Defective Replacement Parts at PT Bonecom Tricom Paintech - Rizki Fahrizal; Sophian Andhika Sardi; Antika Zahrotul Kamalia (Jurnal Teknik Indonesia, 2026)
Developments in information technology have encouraged companies to improve the effectiveness and accuracy of operational data management. PT Bonecom Tricom Paintech still records Not Good (NG) part monitoring manually, which increases the likelihood of recording errors, delays in reporting, and the possibility of data loss. This study aims to design and implement a web-based information system for NG part monitoring using the Implementation of the Rapid Application Development Method in the Development of a Web-Based Information System for Monitoring Defective Replacement Parts at PT Bonecom Tricom Paintech method. The RAD method was chosen because it focuses on rapid system development through an iterative approach, prototyping, and active user participation at every stage of development. The research process includes needs analysis, system design using Unified Modeling Language (UML), application development, and system functional testing. The results indicate that the developed system is able to improve the efficiency of the recording process, reduce errors caused by human factors, and provide NG part monitoring information that is more accurate and integrated. With this system, the Quality Assurance Department can conduct supervision and decision-making more quickly and precisely.